Taxonomic adjustments in Discocactus Pfeiff. (Cactaceae) - Santos, Marianna Rodrigues; Machado, Marlon Câmara; Garcia, Flávia C. P.; Taylor, Nigel P. (Phytotaxa, 2015)
Discocactus petr-halfarii was previously regarded as synonym or subspecies of D. bahiensis. On the basis of field surveys and literature analyses, taxonomic investigations and phylogenetic studies, this species is placed as a subspecies of D. zehntneri. New synonymy is also established for D. heptacanthus.